Pengaruh Pemberian Ekstrak Etanol Daun Ashitaba Terhadap Histopatologi Lambung Mencit Jantan (THE EFFECT OF ETHANOL EXTRACT OF ASHITABA LEAVES TOWARD THE GASTRIC HISTOPATHOLOGY OF MALE MICE) - Wiralaga, I Putu; Sudira, I Wayan; Kardena, I Made; Darmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana, 2015)
This study was intended to find out the effect of ethanol extract of Ashitaba leaves (Angelicakeiskei) toward the gastric histopathology of male mice. After being adapted for one week, 25 malemice (Mus musculus) were divided randomly to be five treatments. The first treatment was not given ethanol extract of Ashitaba leaves as control. The second till fourth treatment was given eachdose of 125; 250; 500; dan 1,000 mg/kg bb during 21 days orally. Necropsy for gastric organharvesting was conducted on the day of 22. The result of giving ethanol extract of Ashitaba leaves(Angelica keiskei) with a dose of 125 mg/kg bb showed that three mice undergo degeneration andinfiltration of inflammatory cells and one mice undergo necrosis. The dosing of 250 mg/kg bbshowed that three mice undergo degeneration and two mice undergo infiltration of inflammatorycells and necrosis as well. The dosing of 500 mg/kg bb showed that three mice undergodegeneration, infiltration of inflammatory cells, and necrosis. The dosing of 1,000 mg/kg bbshowed that three mice undergo degeneration and necrosis, and four mice undergo infiltration ofinflammatory cells. Based on the results of the study, It was concluded that the ethanol extract ofleaves Ashitaba dose of 125 mg / kg bw up to 1,000 mg / kg bw for 21 days did not cause structural disorders of the stomach organ histopathology of mice (Mus musculus) male.
Keywords: ashitaba; gastric; mice